Respuesta :

Answer:

1) shifts f(x) 4 units down  = g(x) = [tex]2x-10[/tex]

2) stretches by factor 4    =  g(x) = [tex]8x-24[/tex]

3) shifts f(x) 4 units right   =  g(x) = [tex]2x-14[/tex]

4) compresses by factor 4 =  g(x) = [tex]8x-6[/tex]

Step-by-step explanation:

1) When we have to move the function down by 4 units, subtract the whole function by -4, that is y -4.

Thus, f(x) becomes  g(x) = [tex]2x-6-(4)[/tex] = [tex]2x-10[/tex]

2) When the function is stretched away from x axis, it means in Y direction.

 Thus, when stretched 4 units in Y direction, the function becomes 4(f(x))

 =  g(x) = [tex]4(2x-6)[/tex] = [tex]8x-24[/tex]

3)When we have to move the function right by 4 units, replace x with (x-4) in the function.

Thus, f(x) becomes  g(x) = [tex]2(x-4)-6[/tex] = [tex]2x-8-6[/tex] = [tex]2x-14[/tex]

4) When the function is stretched towards y axis, it means in X direction.

 Thus, when compressed 4 units in X direction, replace the x by 4x.

 =  g(x) = [tex]2(4x)-6[/tex] = [tex]8x-6[/tex]

Answer:

(-4.5, -3):T

(3.5, 0):R

(-2, 4):P

(4, 6.5):Q

Step-by-step explanation:I dont need proof. the answer i right infront of you

ACCESS MORE